Kosovo Early Childhood Development : SABER Country Report 2021 - World Bank (World Bank, Washington, DC, 2021)
Early childhood development (ECD) has become a high priority for the government of Kosovo in the last decade. Kosovo has a relatively well-established legal framework supporting early childhood development (ECD). Systems Approach for Better Education Results - Early Childhood Development (SABER-ECD) collects, analyzes, and disseminates comprehensive information on ECD policies around the world. In each participating country, extensive multisectoral information is collected on ECD policies and programs through a desk review of available government documents, data and literature, and interviews with a range of ECD stakeholders, including government officials, service providers, civil society, development partners and scholars. The SABER-ECD framework presents a holistic and integrated assessment of how the overall policy environment in a country affects young children’s development. This assessment can be used to identify how countries address the same policy challenges related to ECD, with the ultimate goal of designing effective policies for young children and their families.